A Study of the Charge Transport Process at Nickel Hydroxide-Gold Modified Electrodes employing Rotating Disc Electrode Voltammetry and Ac Impedance Measurements - Tucceri, Ismael Ricardo (2014)
The aim of the present work was study how the charge-transport process of a nickel hydroxide film electrochemically synthesized on a gold substrate is modified when the electrode is stored without use for long time. It was found that nickel hydroxide films deactivate under storage, that is, films become less conductive than immediately prepared ones (nondeactivated). This study was carried out in the context of the Rotating Disc Electrode Voltammetry (RDEV) and Electrochemical Impedance Spectroscopy (EIS) when the modified electrode contacts an electroactive solution and a redox reaction occurs at the Au−Ni(OH)2|ectrolyte interface. Variations of anodic limiting currents with the electrode rotation rate, for both nondeactivated and deactivated films in the presence of the electroactive solute deferasirox (4-(3,5-bis(2-hydroxyphenyl)-1,2,4-triazol-1-yl) benzoic acid) allowed one obtaining a charge transport rate across a nickel hydroxide film, which decreases with the increase of the storage time. Interpretation of impedance spectra obtained at potential values corresponding to the anodic limiting currents on the basis of an impedance model that considers an uniform and nonporous nickel hydroxide film deposited in a conductive substrate and no penetration of redox species (deferasirox) from the solution, allowed one obtaining different interfacial resistances and electron and ion diffusion coefficients for the Au−Ni(OH)2|ectrolyte system.